Tasks, communication and mathematical reasoning: teachers’ professional learning in lesson studies - Quaresma, Marisa; Ponte, João Pedro da (Universidade Estadual de Campinas, 2016)
We analyze the learning about, tasks, communication and ways to promote students’ mathematical reasoning processes made by a grade 5 teacher in a lesson study. Data were collected through an individual and a focus group interview as well as the teacher’s final reflection. The lesson study, combining knowledge from research with teachers’ experiential knowledge, carried out in a collaborative context and exploiting situations of reflection on practice regarding students’ communication and reasoning (sometimes unexpected), represented a favorable context for this teacher professional development, notably on issues relating to communication, tasks and reasoning processes in the teaching and learning of mathematics.